Associação de disfunção temporomandibular e estresse em estudantes universitários - Riffel, Caroline Dias Tams (2013)
Chronic pain is one of the major cause of physical and psychosocial suffering, of work absences and absences because of disability. Temporomandibular disorder (TMD) is an expression used to refer to functional alterations related to the temporomandibular joint (TMJ), affecting all the stomatognathic system. In this perspective, this work is dedicated to the research of the epidemiological profile indicative of TMD and its possible correlation with emotional stress disorder. The study population was composed of 696 students in the areas of Health, Engineering, Applied Social and Linguistics, Letters and Arts, of the UPF. Questionnaires were applied to identify signs of stress and DTM. The results were tabulated and analyzed using descriptive statistics, Spearman correlation and Chi-square test. It was concluded that there is a correlation between TMD and stress, however, this relation has no strength. The differences between the four studied areas were identified, but no statistical differences were noted